The Metropolis and Nose Life. Sensory Memories, Odors and Emotions - Ramos, Olga (Simmel Studies, 2020)
Following Simmel's legacy, the present paper shows how ‘sensory memories’ and emotions are related to the meanings attributed to the smells of human and non-human entities in the metropolis. Based on the findings of a larger research project on urban youth in Mexico City, the article emphasizes how even though the smell is one of the most undervalued senses; it has a significant presence, not only unpleasant but also pleasant memories. In other words, these findings show how ‘sensory memory’ permits a ‘somatic work’ (Vannini et al. 2012) on the sensations and emotions that have persisted in our sensitive bodies, in which smell is not necessarily a “dissociating sense” as Simmel believed, even in the metropolis.